Measuring the Financial Performance of Islamic Commercial Banks Through the Islamicity Performance Index Approach - Harahap, Darwis (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
This study aims to measure the profitability of Islamic commercial banks through the Islamicity Performance Index (profit sharing ratio, zakat performance ratio, directors employees welfare ratio, Islamic income vs. non-Islamic income ratio). This research is quantitative using secondary data. Determination of the sample using a purposive sampling technique, obtained a total sample of 7 Islamic Commercial Banks. The data analysis technique uses the help of the E-Views version 9 method as a calculating tool. The results of the t test show that partially there is an effect of the profit sharing ratio on the profitability of Islamic Commercial Banks, then there is no effect of the zakat performance ratio, directors employees welfare ratio, Islamic income vs. non-Islamic income ratio on the profitability of Islamic Commercial Banks. The Financial Services Authority (OJK), continues to supervise the financial performance of Islamic banks in Indonesia so that the growth and progress of Islamic banks is able to increase profits while providing quality and accurate information and being able to align positions with conventional banking.